(untitled) (European Journal of Pure and Applied Mathematics, 2017)
Let G be a graph and A(G) be its adjacency matrix. The nullity of graph is the presence of zero as an eigenvalue in the spectrum of G. In this paper, we have established the results on nullity of (P_nS_m) where S_m is smith graph and is corona product. Moreover we have shown that nullity of (P_nS_m) depends upon the nullity of S_m, which comes out to be a multiple of nullity of S_m.